Literature Review: The Potential of Phenolic Compounds as Allelopathic Agents in Mangifera indica - Noli, Zozy Aneloi; Nurhafitri, Amanda; Puspita, Ayumi Rizci; Putri, Mellanie Alia; Santoso, Putra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Phenolic compounds are a group of secondary metabolites identified as having significant roles in various ecophysiological processes, including allelopathic activity. In Mangifera indica (mango), phenolic compounds contribute to chemical interactions between plants by releasing allelopathic substances that influence the growth and development of surrounding plant species. This study aims to review the potential of phenolic compounds in M. indica as allelopathic agents, focusing on identifying dominant types of phenolic compounds, allelopathic mechanisms, and their ecological impacts on plant communities. The research method employed is a literature review involving a search for relevant sources on Google Scholar covering the period from 2010 to 2024. Based on a review of various studies, it has been demonstrated that phenolic compounds in M. indica possess significant potential to inhibit the growth of competitors and can be utilized in environmentally friendly agricultural management.